Machine learning approaches for boredom classification using EEG - Seo, Jungryul; Laine, Teemu H.; Sohn, Kyung Ah (Journal of Ambient Intelligence and Humanized Computing, 2019)
Recently, commercial physiological sensors and computing devices have become cheaper and more accessible, while computer systems have become increasingly aware of their contexts, including but not limited to users’ emotions. Consequently, many studies on emotion recognition have been conducted. However, boredom has received relatively little attention as a target emotion due to its diverse nature. Moreover, only a few researchers have tried classifying boredom using electroencephalogram (EEG). In this study, to perform this classification, we first reviewed studies that tried classifying emotions using EEG. Further, we designed and executed an experiment, which used a video stimulus to evoke boredom and non-boredom, and collected EEG data from 28 Korean adult participants. After collecting the data, we extracted its absolute band power, normalized absolute band power, differential entropy, differential asymmetry, and rational asymmetry using EEG, and trained these on three machine learning algorithms: support vector machine, random forest, and k-nearest neighbors (k-NN). We validated the performance of each training model with 10-fold cross validation. As a result, we achieved the highest accuracy of 86.73% using k-NN. The findings of this study can be of interest to researchers working on emotion recognition, physiological signal processing, machine learning, and emotion-aware system development.
Keywords: 10-fold cross-validation; Boredom; Electro-encephalogram (EEG); Emotion; Emotion-aware systems; Machine learning approaches; Physiological sensors; Physiological signal processing; Boredom; Classification; EEG; Emotion; Machine learning; Sensor